Study of Green Supply Chain Implementation in the Sport Shoe Industry in Indonesia to Gain Competitive Advantage - Oetomo, Dedy Setyo; Hermawan, Asep; Widowati, Imas (Sainteks: Jurnal Sain dan Teknik, 2025)
This study examines the implementation of Green Supply Chain Management (GSCM) in the Indonesian sports shoe industry and its impact on the company's competitive advantage. The objectives of the study were to analyze GSCM practices implemented by the Indonesian sports shoe industry, identify factors that influence the success of GSCM implementation, and measure its impact on the company's environmental performance and competitive advantage. The study used a quantitative approach with a survey method on 120 APRISINDO member sports shoe companies. Data analysis used Structural Equation Modeling (SEM) with AMOS software. The results showed that the implementation of GSCM including green purchasing, eco-design, green manufacturing, and reverse logistics had a significant positive effect on environmental performance (β=0.672, p<0.01) and competitive advantage (β=0.583, p<0.01). The main supporting factors for the success of GSCM were top management commitment, green technology capabilities, and collaboration with suppliers. This study provides theoretical and practical contributions to the development of GSCM in the Indonesian sports shoe industry.